Utility of BIM-CFD Integration in the Design and Performance Analysis for Buildings and Infrastructures of Architecture, Engineering and Construction Industry - Kang, Ki-Yeob; Wang, Xiangyu; Wang, Jun; Xu, S.; Shou, W.; Sun, Yanhui (MDPI, 2022)
To scrutinize the current application of building information modelling (BIM) and computational fluid dynamics (CFD) integration in research as well as industrial fields, the present study conducted a holistic review including a bibliometric exploration for existing articles, specific content analysis in different sectors, and follow-up qualitative discussion for the potential of this integrated technology. The bibliometric exploration is focused on analyzing main journals, keywords, and chronological change in representative research content by selecting 115 relevant studies. In content analysis, the representative integrated BIM and CFD application cases are divided into three different sectors. The functionality, interoperability, and sustainability of such integration in architecture, engineering, and construction (AEC) projects are described in detail. Furthermore, the future research based on the applications of BIM and CFD integration is discussed. Specifically, the more advanced hazard analysis is proposed reflecting the strength of such an integration. Comprehensive information for the possible hazards in AEC projects is digitized and quantified to make a more sensitive hazard recognition tool which can formalize reduction strategies and measures of potential hazards. As a result, the present review study contributes to relevant research by identifying representative application parts and practical requirements for BIM and CFD integration in whole design aspects, reviewing the current research trends and future direction in detail, and analyzing the major issues, such as an interoperability in BIM-compatible CFD for sustainable built environments.